139k views
3 votes
Multiply: (x−5)(x−7) A x2−12x+35 B x2+2x+35 C x2+35 D x2+35x−12

Multiply: (x−5)(x−7) A x2−12x+35 B x2+2x+35 C x2+35 D x2+35x−12-example-1
User Drlobo
by
5.5k points

2 Answers

3 votes

Answer:

Explanation:

x*x=2x

x*-7=-7x

-5*x=-5x

-5*-7=+35

2x-12x+35

A

User Frank Rem
by
5.3k points
7 votes

Answer:

x^2 -12x+35

Explanation:

(x−5)(x−7)

FOIL

first x*x = x^2

outer -7x

inner -5x

last -7*-5 = 35

Add them together

x^2 -7x-5x +35

x^2 -12x+35

User Roych
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.